Pengembangan Modul Pembelajaran Matematika Berbasis Contextual Teaching and Learning (CTL) untuk Meningkatkan Komunikasi Matematis Pada Siswa SMP - Adi Saputro; Teguh Wibowo; Prasetyo Budi Darmono (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2025)
AbstrackOne of the abilities that support the mathematics learning process so that it can run well is mathematical communicatin skills. To achieve the learning process it needs to be developed among students. Communication plays a role in the llearning process, including math learning. Environment can be a source f learning mathematics in real life. Mathematics in everyday life is known as Contextual Teaching and Learning (CTL). This research is motivated by the unavailability of mathematics based learning Contextual Teaching and Learning (CTL) in the school according to the background of the problem. The purpose of this research is to produt in the from of a mathemicaal module thaa combines material and everiday life problem. The developen mode used is ADDIE. The reseach produces a module that links mathematics with everiday life problem on the material of linear equations of two variables valid, practical, efective. Keywords: Modules, Contextual Teaching And Learning, Mathematical Communication